Country Partnership Framework for the Republic of Ecuador for the Period of the FY19-FY23 - World Bank Group (World Bank, Washington, DC, 2019)
The Country Partnership Framework (CPF) follows three distinct periods that have framed the World Bank Group’s (WBG’s) relationship with Ecuador. There was an extended period (FY07-FY14) in which the WBG had a limited dialogue with the Government of Ecuador (GoE, the Government), followed by a two-year period in which the policy dialogue, analytical work and lending operations were re-initiated in targeted areas of engagement, under the framework of the FY14-FY15 Interim Strategy Note (ISN). Finally, in early 2016 during a period of uncertainty amidst a rapidly changing context, the WBG Country Engagement Note for the period FY16-FY17 provided the structure for a continued reengagement in limited, focused areas, and helped develop deeper knowledge about Ecuador’s broader development challenges through strategic analytical work that will help advance towards the preparation of a broader, medium-term engagement framework for the WBG. The CPF represents a significant scale up of the WBG’s ongoing engagement in Ecuador and requires the WBG, the World Bank (WB), the International Finance Corporation (IFC) and the Multilateral Investment Guarantee Agency (MIGA) to work in a closely coordinated and complementary fashion in support of the CPF objectives and program. The WB, IFC, and MIGA will continue working together to deliver top quality support to Ecuador’s efforts at building a thriving private sector, and maximize finance for development, including in the design of Development Policy Financing (DPF) operations. In this new context, the WBG will be: (i) front-loading its financial support for the current efforts at macro-stabilization, revival of the private sector, and protection of the poor and vulnerable; (ii) continuing to produce quality and timely Advisory Services and Analytics (ASA); (iii) increasing its partnership with other International Financial Institutions (IFIs) and development partners; (iv) continuing to look for investment opportunities with companies in several sectors (e.g. agribusiness, manufacturing and financial institutions) and where enabling conditions are improved (e.g. mining), and (v) scaling its dialogue with multiple stakeholders in the country, including the private sector and civil society organizations, to assure complementarity and the mutual reinforcement of their agendas. The Performance and Learning Review (PLR), scheduled for FY21, will provide the opportunity to take stock of progress towards CPF objectives and determine how best to adjust, continue, and deepen the WBG’s engagement in Ecuador.